When Aryne Chemistry Meets Organosulfur Compounds - Tan, Jiajing; Feng, Xiaoying; Fan, Rong; Zhuang, Zhe; Guo, Yifeng (Synlett, 2023)
Organosulfur compounds are ubiquitous in agrochemicals, active pharmaceutical ingredients, natural products, catalysts, and functional materials. The efficient assembly of sulfur-containing skeletons through S(IV) intermediates has emerged as an actively explored direction in organic synthesis. In the past 7 years, our research group has been devoted to developing aryne-induced, sulfonium-zwitterion-based synthetic methodologies. In this account, we systematically overview our recent efforts on this topic, including sigmatropic rearrangements, ring opening of cyclic sulfides, and selective S-arylation of thio-oxindoles. These distinct protocols feature mild conditions and avoid the use of transition metals, allowing facile access to structurally diverse organosulfur compounds. The working hypothesis for our reaction design and key historical precedents are also critically discussed. Our goal is to achieve selectivity control and diversity-oriented synthesis, further advancing sulfonium zwitterion chemistry in the direction of precision synthesis.1 Introduction2 Sigmatropic Rearrangement3 Ring Opening of Cyclic Sulfides4 Selective Arylation of Thio-oxindoles5 Conclusion
Keywords: aryne; zwitterion; sulfonium salt; sulfur ylide; organosulfur compound; precision chemistry